(Meth)acrylate copolymers of Eudragit® type in oral tablet technology - Naiserová, Martina; Kubová, Kateřina; Vysloužil, Jakub; Bernatoniene, Jurga; Brokalakis, Iosif; Vetchý, David (Ceska a Slovenska farmacie, 2019)
This review focuses on the characterization of (meth)acrylate copolymers - Eudragit®, describing their thermal treatment behaviour, possible interactions between cationic and anionic polymers, incompatibilities related to Eudragits® and their use in the pharmaceutical technology of oral tablets. In summary, Eudragit® copolymers are divided into soluble ones, insoluble ones and a combination of these two types. The combination of soluble and insoluble poly(meth)acrylate gave a new type of polymer, Eudragit® FL. In oral tablet technology, Eudragits® are widely used in matrix tablets, either alone or in combination, where they mainly provide sustained drug release. To a lesser extent, Eudragits® are used in gastroretentive systems. Moreover, Eudragits® are also of great importance in coated tablets technology, where these enteric polymers provide specific drug targeting to certain parts of the digestive tract, mainly to the small intestine or colon. Important systems such as CODESTM and MMX® technology are mentioned. Last but not least an overview table of currently available oral medicinal products on the Czech market, where at least one of the Eudragits® was used as a film-forming agent, is included.
Keywords: prolonged drug release; farmaceutická chemie; Polymethacrylic Acids; Solubility; Tablets; tablety; colon drug delivery; film-coating tablets; acidoresistant tablets; Eudragit®; floating tablets; burst effect; kyseliny polymethakrylové; Delayed-Action Preparations; matrix tablets; léky s prodlouženým účinkem; Chemistry, Pharmaceutical; rozpustnost